A melhoria do processo de aprendizagem do eletromagnetismo com a utilização de experimentos de baixo custo - Rocha, Carlos Henrique da Silva (2016)
This work aims to analyze the application of Electromagnetism of the education proposal, in the third year of high school, covering the use of low cost experiments during the course of lessons. The strategies employed seek a job that prioritizes the physical concepts to the detriment of the approaches only with mathematical tools, enabling students to more active participation in the learning process. This approach meets the proposals of the National Curriculum Standards in order to present alternative forms of education that make the most attractive classes, more effective, enjoyable and motivating, that is, closer to the reality of students. This research was developed with two high school classes of a Technical School located in the city of Rio de Janeiro during the third stage of the school calendar of the school year 2015. The theoretical framework was used the Theory of Conceptual Fields of Gérard Vergnaud and current research Experimentation in Physics Teaching in the area. As a partial evaluation of the implementation of this proposal may be mentioned that students were more motivated when presented to the concepts of electromagnetism with the help of experiments and demonstrated better understanding of the concepts from the tests applied to the end of the meetings. Regarding the analysis of conductor teacher, he held classes with performing experiments a fruitful environment for mediation and conceptualization. As an educational product of this work, in addition to the thesis, the experiments will be developed (Experimental Kit) and a Didactic sequence that enables your application.